1975
DOI: 10.1139/z75-094
|View full text |Cite
|
Sign up to set email alerts
|

Avian Leucocytozoidae. I. Morphometric variation in three species of Leucocytozoon and some taxonomic implications

Abstract: The variability of nine morphometric parameters of Leucocytozoon simondi, L. dubreuili, and L. fringillinarum was studied with respect to variability (a) within a single bird; (b) within a single bird at different times; (c) between different birds of the same species: (d) between the same species of birds of different populations; and (e) between different species of birds. The results indicated that the variability of the parasites was of the same order of magnitude for all situations studied. Leucocytozoon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Three species of Leucocytozoon are generally accepted as commonly occurring in passeriform birds: L. majoris, L. dubreuili and L. fringillinarum (Bennett and Cameron 1975), many of the other described species having been shown at least morphologically, to be synonyms of the last (Bennett and Campbell 1975). Mixed infections with two and even all three species are common (Bennett and Cameron 1975), which often makes definitive diagnosis difficult when only a few parasites are present which do not clearly conform morphologically to the criteria generally accepted as separating the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three species of Leucocytozoon are generally accepted as commonly occurring in passeriform birds: L. majoris, L. dubreuili and L. fringillinarum (Bennett and Cameron 1975), many of the other described species having been shown at least morphologically, to be synonyms of the last (Bennett and Campbell 1975). Mixed infections with two and even all three species are common (Bennett and Cameron 1975), which often makes definitive diagnosis difficult when only a few parasites are present which do not clearly conform morphologically to the criteria generally accepted as separating the species.…”
Section: Discussionmentioning
confidence: 99%
“…Although Bennett and Campbell (1975) relegated seven species of Leucoeytozoon to synonyms of L. fringillinarum, one species not treated thus was L. brimonti (Mathis and Ldger 1910a) Kenya, Tanzania, Zaire and Ghana (Peirce et al 1977a, Bennett and Herman 1976, Wink and Bennett 1976. However, in the Mascarene Islands Peirce et al (1977b) considered the leucocytozoid found in Pycnonotidae to be indistinguishable from L. fringillinarum.…”
Section: Discussionmentioning
confidence: 99%
“…A more critical review of the literature indicates, however, that (1) three of the transmission attempts cited were not from published papers, but rather were "personal communications" and are of doubtful scientific value since details are not available; (2) one of the citations (Fallis and Bennett 1958) was incorrect; that is, it contained no information on the attempted transfer of Leucocytozoon bonasae from grouse to ducks and sparrows, rather they transferred L. bonasae from grouse to grouse; (3) the statement that Fallis et al (1973) failed to transfer L . schoutedeni from chickens to guinea fowl and Leucocytozoon neavei from guinea fowl to chickens was Source: Prepared from data presented by Bennett and Campbell (1975), Greiner and Kocan (1977), Bennett et al (1982Bennett et al ( , 1992a, Bishop and Bennett (1992), Forrester et al (1994), Super and van Riper (1995), Rintamäki et al (1999), Adlard et al (2002Adlard et al ( , 2004, Valkiūnas et al (2002), Savage (2004), Savage et al ( , 2006a, Jones et al (2005), Peirce et al (2005), and Valkiūnas (2005).…”
Section: Etiologymentioning
confidence: 99%
“…Only undistorted. round forms were measured across the parasite at the point where it is not covered by the host cell nucleus (measurement D2 in Bennett & Campbell 1975). The mean measurements of both macro-and microgametocytes from jackass penguins are significantly larger than those given by Fallis et al (1976) in the original description of the species from the Fiordland crested penguin ( Table 1).…”
mentioning
confidence: 94%
“…The reason for this is not clear but because Fallis et al (1976) did not state exactly how measurements were made it is difficult to compare directly those from the jackass and Fiordland crested penguins. There can be a great variation in the size of several Leucocytozoon species, even at different times of infection in the same bird (Bennett & Campbell 1975), which may also account for the size difference. The dimensions were re-measured from the parahapantotype • Calculllled from the dala given by Fallis a al.…”
mentioning
confidence: 99%